Penerapan Pembelajaran Mind Mapping untuk Meningkatkan Pemahaman Siswa Terhadap Materi Pelajaran Fiqih Kelas VII di MTS Nur Ibrahimy Enoman - Cut Vica Ziara Putry; Hairul Huda; Sofyan Rofi (CV. Lentera Literasi Indonesia, 2025)
The learning process of Fiqh subjects at the Madrasah Tsanawiyah level is often dominated by conventional lecture methods, which tend to reduce students’ active participation and hinder their deep understanding of religious concepts. This becomes a significant challenge for teachers in delivering materials that are expected to be understood not only theoretically but also applied in daily life. Based on this condition, the present study aims to evaluate the effectiveness of the Mind Mapping method in improving students’ understanding of Fiqh subject matter in Class VII of MTs Nur Ibrahimy Enoman, Situbondo. This research adopts a qualitative approach using a case study method through observation, interviews, and documentation techniques. The findings indicate that the implementation of Mind Mapping significantly enhances students’ cognitive understanding, as shown by their improved ability to organize and explain the material systematically and creatively. Furthermore, affective aspects such as learning enthusiasm, a sense of responsibility, empathy, and self-confidence also improved. These results suggest that Mind Mapping is not only theoretically effective but also practically applicable, particularly in the context of Islamic religious education. It provides a strategic alternative for teachers to foster active, meaningful, and enjoyable learning experiences.